1997
DOI: 10.1039/a602148d
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dielectric study of the Na0.5Bi0.5TiO3–PbTiO3 and K0.5Bi0.5TiO3–PbTiO3 systems

Abstract: A study of the Na0.5Bi0.5TiO3-PbTiO3 and K0.5Bi0.5TiO3-PbTiO3 systems has been carried out using Xray diffraction, differential scanning calorimetry and dielectric measurements. The limits of the rhombohedral (Na0.5Bi0.5TiO3-rich side) and tetragonal (PbTiO3-rich side) solid solutions have been determined, as well as the evolution of their lattice parameters as a function of composition and temperature. Ceramic materials have been prepared by natural sintering (1090-1220 °C; 0.5 h) of powders obtained by solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 8 publications
1
36
0
1
Order By: Relevance
“…As the composition of a phase boundary is largely dependent on the degree of lattice distortion of the solid solution end-members [6], the phase transition in NBPT(x) occurs on the sodium-rich side due to the relatively large lattice distortion of PbTiO 3 . This has been confirmed by earlier studies on NBPT(x) bulk ceramics [3,5,7,8]. However, there are several large discrepancies concerning the compositions of these phase transitions in the system.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…As the composition of a phase boundary is largely dependent on the degree of lattice distortion of the solid solution end-members [6], the phase transition in NBPT(x) occurs on the sodium-rich side due to the relatively large lattice distortion of PbTiO 3 . This has been confirmed by earlier studies on NBPT(x) bulk ceramics [3,5,7,8]. However, there are several large discrepancies concerning the compositions of these phase transitions in the system.…”
Section: Introductionsupporting
confidence: 83%
“…For instance, although some investigators proposed the existence of a morphotropic phase boundary (MPB), very differing compositions (i.e., x=0.1, 0.13 and 0.13-0.15) have been reported for the MPB [3,7,8]. Moreover, Elkechai et al [5] suggested a biphasic region of 0.1 < x < 0.18 in the same system. Although several of these discrepancies have been widely attributed to the microstructure features arising from different synthesis processes, a detailed, systematic study is required, in order to properly understand the nature, compositions and characteristics of these phase transitions.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The room temperature tetragonality c/a changes from 1.06 for PT to 1.02 for the maximum of NBT solubility (NBT82-PT18), the decrease being more pronounced when the NBT content becomes larger than 30 mol% as shown in Fig. 4 [14]. Such a behaviour appears in the observed evolution of the Raman spectra with the composition.…”
Section: Room Temperature Behaviourmentioning
confidence: 58%
“…5. Taking into account that (i) the tetragonal symmetry exhibited by the solid solutions decreases as the NBT content increases and (ii) the band at 280 cm À 1 is dominated by the Ti -O vibrations, such a coalescence of the two bands was expected with respect to the XRD data [6][7][8]14]. As for the bands located in the 450 -700 cm À 1 , they broaden and are shifted upwards.…”
Section: Room Temperature Behaviourmentioning
confidence: 93%